If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 8 = -32 Reorder the terms: 8 + 5p = -32 Solving 8 + 5p = -32 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 5p = -32 + -8 Combine like terms: 8 + -8 = 0 0 + 5p = -32 + -8 5p = -32 + -8 Combine like terms: -32 + -8 = -40 5p = -40 Divide each side by '5'. p = -8 Simplifying p = -8
| 2=-19+z | | 6m-4=4m | | 2=-4+k | | 18p^3-63p^2-9p=0 | | 4x^2+8x+48y-44=0 | | -7(2x-8)+3=-14x+59 | | 10-4=16 | | Q-3=25 | | F(x)=ln(x)*x^2 | | 66=10-8b | | K-12=11 | | b/2=-7 | | 4b+3a= | | 1-2r=9-r | | 12x^4-26x^3+10x^2=0 | | 9x-2=9(x+8) | | 8=6-p(p+3) | | 2x(6x^3-13x^2+5x)=0 | | 8y^3+6y^2-9y= | | 5(32n-40)=4(5n+1) | | x=2(1-x) | | p+12=-5 | | 22x+3x^2=-40 | | 5x+7=5(X+2) | | (4x+9)+(3x-12)+2x=180 | | 3k-12=2k+10 | | 46x-14x^2-12=0 | | 2(q)+5(1-q)=6q+1(1-q) | | 2p-17=2(p-3)+9 | | 3x^2+22x+40=0 | | 6(5-4x)=-18 | | -7x^2+14x=x |